Pengaruh Eksplorasi Trend Flexible Working Arrangement dan Penggunaan Teknologi Informasi Di Kalangan Generasi Z - Nur Fatimah; Indra permana; Muhammad Ekhsan (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
Abstract The Covid-19 pandemic has brought many changes to life, especially in terms of work. The limited space available during the pandemic means that many companies have to look for various ways to remain productive even in the face of many limitations. The company optimizes technological advances by implementing an all-digital work system, with this work system employees can still be productive even when they are far from each other. The purpose of this research is to find out how influential the Flexible Working Arrangement Trend and the use of technology are on Generation Z. This research method uses quantitative methods, namely distributing questionnaires to employees who fall into the criteria for Generation Z in the Jabodetabek area. The data obtained was then processed using SPSS. The results of this research are that the Flexible Working Arrangement variable (X1) has an influence on the generation z (Y) variable in the Jabodetabek area. And it was declared significant because of the t-statistic value (0.000<0.05). The Information Technology Use variable (X2) also has an influence on the generation z (Y) variable in the Jabodetabek area and is declared significant because of the t-statistic value (0.000<0.05). This research provides results that the Flexible Working Arrangement Trend and the use of technology have a positive influence. This is due to several factors, namely comfort, effectiveness, ease of discipline in carrying out tasks to achieve targets. Keywords: Flexible working, Technology, Generation Z